Analysis of the Influence of Good Corporate Governance and Intellectual Capital on Financial Performance (Studies of Entertaintment and Media Industry Companies Listed on the IDX in 2014-2021) - Hanifarya Beta; Meily Kalalo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to examine the impact of good corporate governance and intellectual capital on the financial performance of entertainment and media companies listed on the Indonesia Stock Exchange from 2014 to 2021. Good corporate governance is measured using the good corporate governance index, while intellectual capital is measured using the VAICTM. This study adopts a quantitative research approach and utilizes secondary data. The sampling technique employed is non-probability sampling with a purposive sampling method. The samples obtained from the selection results were 4 companies. Logistic regression is used as the data analysis technique in this research, utilizing SPSS 26 software. The findings of this study indicate that good corporate governance does not have a significant impact on financial performance, whereas intellectual capital has a positive and significant impact on financial performance.